REVITALISASI PENDIDIKAN KEWARGANEGARAAN MELALUI MODEL BELAJAR PRAKTIK BELAJAR KEWARGANEGARAAN (PROJECT CITIZEN) - PH, Rima Vien (PKn Progresif, 2012)
In addition to civic knowledge, Project Citizen aims to foster the skills necessary for citizenship kewargangaraan democracy. Various aspects of the program and student interaction with their classmates, government representatives, and non-governmental organizations at the time of intensive research on community problems allows the students have many opportunities to apply the intellectual skills and abilities to participate. Furthermore, through their participation in Project Citizen, students have the opportunity to develop a variety of civic character of a democratic society such as the meaning of political values??, political interests, political tolerance, commitment to the exercise of democratic citizenship, commitment to civic responsibility, commitment to constitutionalism, and the tendency to participate. The characteristics of these traits, which can be developed through Project Citizen, encourage responsible participation and effective by the citizens in a democracy which they run.